PENERAPAN EDITING CUT TO CUT DALAM FILM PERSETERUAN - I Kadek Galang Chandra Deva; I Dewa Made Darmawan; I Nyoman Payuyasa (CALACCITRA: JURNAL FILM DAN TELEVISI, 2023)
Feud, is a short film in the action drama genre that tells the story of an older brother who tries to save his younger sibling from criminals who are after their parents' land certificate. The author has a duty as an editor or image arranger. In its application, the writer tries to use standard cutting techniques (cut to cut) in presenting storytelling in the film Feud. Cut to cut itself is a simple cutting technique and is most used by other editors. By using the cut to cut technique, the mood development in the film becomes more interesting and gives a meaningful feel to the story. In writing, the author uses several theories from various sources such as Rosenberg which explains the cut theory, Thomson and Bowen which explains the responsibilities of an editor. And J.M Peters who explained about editing theory. In the application of the cut to cut editing technique, the author first conducts a preview of each shot which will later be included in the editing application, and when all the shots are deemed perfect, the author as the editor then arranges each of these shots so that they become an arrangement of images that tell a story.